Whitehead groups of finite groups - Oliver, Robert 1949- (Cambridge University Press, 1988)
This book's aim is to make accessible techniques for studying Whitehead groups of finite groups, as well as a variety of related topics such as induction theory and p-adic logarithms. The author has included a lengthy introduction to set the scene for non-specialists who want an overview of the field, its history and its applications. The rest of the book consists of three parts: general theory, group rings of p-groups and general finite groups. The book will be welcomed by specialists in K- and L-theory and by algebraists in general as a state-of-the art survey of the area
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Whitehead groups; Finite groups; Induction (Mathematics); Endliche Gruppe; Whitehead-Gruppe